Contradictory Depictions of the New Woman: Reading Edith Wharton’s The Age of Innocence as a Dialogic Novel - Sevinc Elaman-Garner (European Journal of American Studies)
Critical debate pertaining to the themes of gender and marriage in Edith Wharton’s The Age of Innocence (1920) has often focused on May and Ellen as the representation of two contrasting images of female identity: “angelic” and “monstrous” respectively. Drawing on Mikhail Bakhtin’s concept of dialogic novel, this article offers an alternative reading. In particular, it aims to examine the previously overlooked complexities in the novel’s decentered narrative, notably its dialogic form in which a multiplicity of contending voices and perspectives on women, marriage and divorce are juxtaposed. By adopting this theoretical and methodological stance, the article offers fresh analytical perspectives on the novel and argues that, by depicting Ellen’s performances of shifting subjectivities (the rebel who is seeking a divorce, the unfortunate victim of an unfaithful husband, the lover who desires a new life), the novel not only undermines the dominant ideologies of Victorian womanhood but also disrupts the image of the radical, independent New Woman who challenges social conventions.